2016
DOI: 10.1038/ncomms11385
|View full text |Cite
|
Sign up to set email alerts
|

The PDGF-BB-SOX7 axis-modulated IL-33 in pericytes and stromal cells promotes metastasis through tumour-associated macrophages

Abstract: Signalling molecules and pathways that mediate crosstalk between various tumour cellular compartments in cancer metastasis remain largely unknown. We report a mechanism of the interaction between perivascular cells and tumour-associated macrophages (TAMs) in promoting metastasis through the IL-33–ST2-dependent pathway in xenograft mouse models of cancer. IL-33 is the highest upregulated gene through activation of SOX7 transcription factor in PDGF-BB-stimulated pericytes. Gain- and loss-of-function experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 52 publications
3
100
0
1
Order By: Relevance
“…Depletion of pericytes in tumor vessels by genetic targeting or PDGFR inhibitors facilitated tumor metastasis (46,47). On the other hand, pericytes are required for promoting tumor metastasis by interacting with tumor-associated macrophages (48) or transiting to fibroblasts (49). Consistently, our studies showed that Z-GP-DAVL-BH induced a remarkable reduction of lung metastasis in the MDA-MB-231 breast cancer orthotopic transplantation xenografts.…”
Section: Discussionsupporting
confidence: 77%
“…Depletion of pericytes in tumor vessels by genetic targeting or PDGFR inhibitors facilitated tumor metastasis (46,47). On the other hand, pericytes are required for promoting tumor metastasis by interacting with tumor-associated macrophages (48) or transiting to fibroblasts (49). Consistently, our studies showed that Z-GP-DAVL-BH induced a remarkable reduction of lung metastasis in the MDA-MB-231 breast cancer orthotopic transplantation xenografts.…”
Section: Discussionsupporting
confidence: 77%
“…This finding is in agreement with the recently published data from serous ovarian cancer where perivascular PDGFR- β was also associated with shorter survival (Corvigno et al , 2016). Experimental studies have detected pro- as well as anti-metastatic effects of the perivascular cells (Xian et al , 2006; Cooke et al , 2012; Keskin et al , 2015; Yang et al , 2016). Concerning the pro-metastatic effects, mechanisms were proposed, including IL-33-dependent recruitment by perivascular cells of pro-metastatic TAMs (Yang et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, depletion of pericytes in experimental primary tumours has been shown to enhance metastatis through mechanisms possibly involving tumour hypoxia and enhanced cancer cell intravasation (Xian et al , 2006; Cooke et al , 2012; Keskin et al , 2015). Other studies have instead noted prometastatic effects of PDGFR- β -positive pericytes (Yang et al , 2016). Finally, reduced perivascular coverage has been shown to facilitate infiltration of tumours by immune-suppressive myeloid-derived suppressor cells, ultimately leading to reduced immune-surveillance and increased tumour growth (Hong et al , 2015).…”
mentioning
confidence: 99%
“…MDSC accumulation in tumors led to increases in tumor growth, whereas restoring the PC coverage in tumors abrogated the increased MDSC trafficking to PC-deficient tumors (96). Though, another study reported that IL-33 produced by PDGF-B-stimulated PC promoted metastasis through recruitment of tumor-associated macrophages in several human and mouse graft tumor models (100). Further extensive studies will be required to understand the crosstalk of PC with immune cells different from T cells.…”
Section: Immune Regulation By Pc In the Tumor Microenvironmentmentioning
confidence: 99%